(untitled) (ACME, 2025)
The twenty-one βασιλικοὶ λόγοι written and pronounced by Michael Psellos (1018 – 1078), unedited until the second half of 19th century, saw various editiones principes until the 1980s; they were then collected in an unique Teubner volume in 1994, by George T. Dennis, under the title of Orationes panegyricae; although this volume is the Psellian panegyrics’ edition of reference nowadays, it presents several problems: orations’ order out of phase with actual timeline, the absence of other five orations (anyway collected in the Oratoria minora by Littlewood), very frequent wrong readings from manuscripts and often non-relevant apparatus fontium with author’s achievements. With the help of the numerous studies on Psellos published during the last twenty years, the purpose of this paper is to provide a preparatory study to a new critic edition, by highlighting and overcoming all the problems of the previous Teubner editions.